RETRACTED: Digital twin–driven design and testing of laser shock processed aluminum–graphene composites for spacecraft docking tribology - Hosamane Guruswamy Prashantha Kumar; Praveen Kumar Kanti; Dinesh Dishana; Pratik Shukla; Prabhu Paramasivam; Leliso Hobicho Dabelo (PLoS ONE, 2025)
The study presents the laser shock processed (LSP) aluminum–graphene composite development and performance evaluation as a solution for spacecraft docking systems that require high tribological reliability under vacuum and extreme thermal conditions. Hot extrusion produced a 0.02 wt% single-layer graphene composite that received LSP treatment using 3J energy with 70% pulse coverage degree. Post-LSP treatment showed both good graphene distribution across the material and refined grains throughout the surface. The treatment of LSP raised the Vickers hardness levels of the composite by 28% above the untreated sample’s outcome. The wear rate diminished by 42% under 60 N force and 0.15 m/s sliding speed in vacuum conditions. An improvement of 33% occurred in the sliding performance after LSP treatment because the COF reduced from 0.30 to 0.20. The constructed Python-based digital twin model employed multi-variable regression analysis for 30 experimental trials yielding an R² value of 0.91 and an RMSE value of 0.026 mm³/N·m. The predictive model results matched up with experimental data points within 5–8 percent ranges. Surface integrity along with wear resistance in aluminum alloys improves substantially through the application of LSP with graphene reinforcement which makes them appealing for space docking system mechanical components.